(untitled) (Research, Society and Development, 2025)
The exponential expansion of social media has transformed communication, identity construction, and access to information. However, growing evidence shows that excessive use may contribute to anxiety, depression, low self-esteem, eating disorders, and exposure to cyberbullying. This article aims to analyze the positive and negative mental health impacts of social media use across different age groups. A narrative literature review was conducted in PubMed, Scielo and BVS databases, including studies published between 2017 and 2025. Results show that usage time, engagement patterns, interaction quality and individual psychological characteristics play a central role in determining outcomes. Although risks are predominant in certain contexts, social media also offer benefits such as health information dissemination, emotional support and community building. We conclude that impacts depend on how platforms are used, moderated, and integrated into everyday life. Strengthening digital education, parental monitoring, and psychosocial interventions is crucial to mitigate harms and promote healthier online environments.